Repeatability and Predictability of Calf Feeding Behaviors—Quantifying Between- and Within-Individual Variation for Precision Livestock Farming - Carslake, Charles; Occhiuto, Francesca; Vázquez-Diosdado, Jorge A.; Kaler, Jasmeet (Frontiers in Veterinary Science, 2022)
Individual calves show substantial between- and within-individual variation in their feeding behavior, the existence and extent of which is not fully researched. In this study, 57 196 feeding records, collected by a computerized milk feeder from 48 pre-weaned calves over 5 weeks, were collated and analyzed for individual differences in three different feeding behaviors using a multi-level modeling approach. For each feeding behavior, we quantified behavioral variation by calculating repeatability and the coefficient of variation in predictability. Our results indicate that calves differed from each other in their average behavioral expression (behavioral type) and in their residual, within individual variation around their behavioral type (predictability). Feeding rate and total meals had the highest repeatability (>0.4) indicating that substantial, temporally stable between individual differences exist for these behaviors. Additionally, for some behaviors (e.g., feeding rate) calves varied from more to less predictable whereas for other behaviors (e.g., meal size) calves were more homogenous in their within-individual variation around their behavioral type. Finally, we show that for individual calves, behavioral types for feeding rate and total meals were positively correlated which may suggest the existence of an underlying factor responsible for driving the (co)expression of these two behaviors. Our results highlight how the application of methods from the behavioral ecology literature can assist in improving our understanding of individual differences in calf feeding behavior. Furthermore, by uncovering consistent between individual behavioral differences in calves, our results indicate that animal personality may play a role in driving variability in calf feeding behavior.